Relationship between peer relations, general self-concept and life satisfaction among adolescents in an international school in Selangor, Malaysia - Chong, Ling Li (2017)
The present study aimed to examine the relationships between peer relations, general self-concept and life satisfaction among adolescents in Selangor, Malaysia. This study also examined the mediating effect of general self-concept in relationships between peer relations and life satisfaction. The present study applied multi-stage cluster sampling and a total of 153 respondents aged between 14- to 17-year old were included for final data analyses. Empirical data were collected through a selfadministered questionnaire that constituted by three instruments (i.e., Positive Relations with Other Scale, general items from Self-Description Questionnaire II, and Multidimensional Students’ Life Satisfaction Scale). The results of the study showed that adolescents were moderately satisfied with their life. Findings from Pearson Correlation revealed that peer relations, and general self-concept were positively related with life satisfaction. Furthermore, the results of the multiple regression demonstrated that peer relations emerged as the strongest unique predictor of life satisfaction, followed by general self-concept, and age. A total of 43.7% of the variability in life satisfaction could be predicted by peer relations, general self-concept, and age. The results also showed that general self-concept significantly mediated the effects of peer relations on life satisfaction. Overall, study contributes to the fundamental understanding of Selangor adolescents’ development, specifically on life satisfaction. The findings from this study may provide useful information regarding adolescents’ life satisfaction to educators, policy makers, parents and caregivers, counsellors and professionals who work closely with adolescents.